2011
DOI: 10.1002/aoc.1792
|View full text |Cite
|
Sign up to set email alerts
|

Imidazole‐coordinated monodentate NHC–Pd(II) complex derived from proline and its application to the coupling reaction of arylboronic acids with carboxylic acid anhydrides in water at room temperature

Abstract: Cleavage of a C-N bond of imidazolium salt derived from N-phenyl-substituted proline was observed in this laboratory. A novel imidazole-coordinated monodentate NHC-Pd(II) complex 5 was obtained as the sole product in good yield in the reaction of imidazolium salt 4 with Pd(OAc) 2 in refluxing THF. The structure of complex 5 was determined unambiguously by an X-ray diffraction. The complex was found to be a good catalyst in the cross-coupling reaction of arylboronic acids with carboxylic acid anhydrides in wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Traditional palladium catalysts for the coupling of arylboronic acids with anhydrides have been recently successfully replaced by new generation catalysts. For example, the use of coordinated monodentate NHC–Pd(II) complex derived from N -phenyl substituted proline has been reported by Shao in 2011 in the coupling reaction of arylboronic acids with benzoic anhydride in water [ 38 ], and cyclopalladated ferrocenylimines catalysts have been recently explored by Wu and coworkers [ 39 ] in the cross-coupling of arylboronic acids with carboxylic anhydrides ( Figure 1 ).…”
Section: Suzuki-miyaura Coupling Of Acyl Chlorides and Anhydridesmentioning
confidence: 99%
“…Traditional palladium catalysts for the coupling of arylboronic acids with anhydrides have been recently successfully replaced by new generation catalysts. For example, the use of coordinated monodentate NHC–Pd(II) complex derived from N -phenyl substituted proline has been reported by Shao in 2011 in the coupling reaction of arylboronic acids with benzoic anhydride in water [ 38 ], and cyclopalladated ferrocenylimines catalysts have been recently explored by Wu and coworkers [ 39 ] in the cross-coupling of arylboronic acids with carboxylic anhydrides ( Figure 1 ).…”
Section: Suzuki-miyaura Coupling Of Acyl Chlorides and Anhydridesmentioning
confidence: 99%
“…Recent studies have showed that N-heterocyclic carbenemetal complexes derived from proline were e cient catalysts in C-C coupling reactions such as Suzuki-Miyaura and Mizoroki-Heck coupling reactions [5][6][7][8][9]. The central palladium atom in the title complex is coordinated by one carbene ligand and the N atom in the pyrrolidine ring, which is also coordinated with two bromine atoms to give the nearly square planar coordination mode, as shown in the gure.…”
Section: Discussionmentioning
confidence: 99%
“…According to the recent contributions from Shao's group, the conclusion can be drawn that N-heterocyclic carbenepalladium and -rhodium complexes derived from the commercially available proline skeleton are useful catalysts in the C-C bond formations performed in neat water under mild conditions [5][6][7][8]. The central palladium atom in the title complex is coordinated by four ligand atoms: one carbene moiety, the N atom in the pyrrolidine moiety and two chlorido ligands to give a very slightly twisted square planar coordination mode.…”
Section: Discussionmentioning
confidence: 99%